2017
DOI: 10.1051/matecconf/201710102012
|View full text |Cite
|
Sign up to set email alerts
|

Storage tank materials for biodiesel blends; the analysis of fuel property changes

Abstract: Abstract. Fuel stability is one of major problem in biodiesel application. Some of the physical properties of biodiesel are commonly changed during storage. The change in physico-chemical properties is strongly correlated to the stability of the fuel. This study is objected to observe the potential materials for biodiesel storage. The test was conducted in three kinds of tank materials, such as glass, HDPE, and stainless steel. The fuel properties are monitored in 12 weeks, while the sample was analyzed every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The corrosion process of fuel containers was simulated through immersion tests in biodiesel. Aluminum and stainless steel are compatible metallic materials for biodiesel containers although stainless steel is the most recommended for this purpose [17]. In this study, in order to understand if metal releasing from the surface during the corrosion process causes an influence on biodiesel stability immersion tests of AISI316 in biodiesel and its blend (B7) were carried out.…”
Section: Corrosion Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion process of fuel containers was simulated through immersion tests in biodiesel. Aluminum and stainless steel are compatible metallic materials for biodiesel containers although stainless steel is the most recommended for this purpose [17]. In this study, in order to understand if metal releasing from the surface during the corrosion process causes an influence on biodiesel stability immersion tests of AISI316 in biodiesel and its blend (B7) were carried out.…”
Section: Corrosion Testmentioning
confidence: 99%
“…However, container material selection should take into account the fact that metal ions may cause biodiesel oxidation [8,9,16]. According to Komariah et al [17], only stainless steel and aluminum are metallic materials compatible with biodiesel and recommended for its storage. Although aluminum is advised as container materials, some studies [10,12] have demonstrated that it is more corrosive (up to 13.5 times higher than stainless steel).…”
Section: Introductionmentioning
confidence: 99%
“…It found that the stability of biodiesel for 180 days of storage showed that exposure to metals also increased the rate of degradation and exposure to higher temperatures in pro-oxidizing conditions accelerated loss of stability [10][11][12][13][14][15]. Previous researcher also found that sunlight give higher increasing rate of acid value and antioxidant gave a significant increase in kinematic viscosity which reflects from different storage condition [5][6]. Furthermore, it has been identified that biodiesel oxidized and degraded faster than diesel oil is changed during storage.…”
Section: Introductionmentioning
confidence: 95%
“…The storage stability of biodiesel was studied since 1985, exposure to heat and air greatly accelerated degradation of biodiesel, but when stored at 20 °C in closed containers or stored after the addition of an antioxidant, the biodiesel remained stable. Furthermore, researcher monitored the production of acids, peroxides, and aldehydes, as well as increase in viscosity induction storage time over a period of 90 days [5][6][7][8][9]. It found that the stability of biodiesel for 180 days of storage showed that exposure to metals also increased the rate of degradation and exposure to higher temperatures in pro-oxidizing conditions accelerated loss of stability [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The microorganisms can develop in fuel systems and grow faster in warm and hot conditions. The risks of diesel fuel contamination get higher as it located in high humidity regions [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%